COMUNICAÇÃO E PROCESSOS DE CONSUMO NA CULTURA FÃ: ANÁLISE DOS COMENTÁRIOS CRÍTICOS NO LANÇAMENTO DE STAR WARS BATTLEFRONT II - PARMIGIANI, THIÉRRI (2019)
This essay presents a study about the critical behavior of the Star Wars fan community regards the launch of the game Star Wars Battlefront II, published by Electronic Arts in 2017. After a controversy involving methods of monetization of the game shortly before its launch, many users complained on social networks and the repercussion caused the company to step back in its marketing practices. The research presents a study on fan identity and critical studies related to the business model of the gaming industry. Based on this reference was made an nethnographic research in the comment area of the official trailer of the game where a great volume of comments was made using a critical look to blame EA Games and market practices, thus absolving Star Wars and Disney.